NAHOTA V KONTEXTU POHYBOVÉ KULTURY [NAKEDNESS IN CONTEXT OF MOVEMENT CULTURE] - Ivo Jirásek (Palacký University Olomouc, 2009)
Příspěvek se zabývá tématem v kinantropologii ne zcela tematizovaným, totiž fenoménem nahého těla v prostředí pohybové kultury. V jednotlivých oblastech tohoto kulturního subsystému (sport, pohybová výchova, pohybová rekreace, pohybová terapie a pohybové umění) upozorňuje na různost významů a kontextů dodávajících nahotě smysl na linii kontinua od přirozenosti a funkčnosti přes erotizaci a sexualizaci až k pornoizaci zejména sportovního prostředí. Autor preferuje funkční přirozenost nahoty a odmítá zvěcnělou pornoizaci těla v pohybu, překračující tak již charakteristiky sféry pohybové kultury. [The paper deals with topic no really thematizing in kinanthropology, namely naked body phenomenon in environment of movement culture. It highlights in particular spheres of this culture subsystem (sport, movement education, movement recreation, movement therapy and movement art) at variety of senses and contexts which give the meaning to nakedness at continuum from naturalness and functionality through erotization and sexualization even to pornoization especially of sport environment. The author prefers the function naturalness of nakedness and he rejects the instrumentalization and change the body into thing in pornoization of body in movement, which exceeds the characteristics of movement culture sphere.]